(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate AFP, CEA and CA 19-9 levels in patients with HCC and non-HCC cirrhosis, and also to investigate the relationship between tumor radiological and clinical characteristics and these markers.Material and Methods: 572 patients with cirrhosis who were followed for cirrhosis between January 2010 and January 2019 in the gastroenterology outpatient clinic of Demiroglu Bilim University Faculty of Medicine were included in the study. Demographic (age, gender, BMI), laboratory (AFP, CEA, CA 19-9) and imaging findings of the cases were retrospectively screened and recorded. The patients were divided into two main groups as HCC and without HCC.Results: In the study, 252 patients were HCC and 320 patients were non-HCC. AFP values and male gender ratio were higher in HCC group, whereas CEA and CA 19-9 values were similar between the two groups. (respectively, p 0.001; p 0.013; p=0.157; p=0.294). A significant positive correlation was found between tumor size and AFP levels, but no correlation was found between CEA and CA 19-9 and tumor sizes. (for AFP r=0.202, p 0.001). CEA level was significantly higher in patients with macrovascular invasion (p =0,011). Conclusion: In our study, positive correlation was found between tumor size and AFP levels in patients with HCC, and a significant correlation was found between CEA and macrovascular invasion. Our study showed that AFP and CEA are valuable markers that can be used to determine prognosis and survival in HCC patients.